Fluctuations in Fruit Fly Population (Bactrocera spp.) and Its Relationship to Environmental Conditions in Red Guava Plantations in Sidoarjo Regency - Indra Djiwanata; Noni Rahmadhini; Herry Nirwanto (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Crystal guava (Psidium guajava) is a superior variety cultivated in Indonesia. A major constraint in crystal guava production is the high incidence of pest attacks, particularly from fruit flies. This study was conducted in a red guava orchard located in Sidoarjo Regency and Jalan Simorejosari A IV/17 during the period from July to August. The research employed a survey method involving the installation of attractant traps and purposive sampling to collect infested fruit for host rearing. Both trapping and host rearing were used to monitor the fruit fly population. Trapping was carried out by installing attractant traps at five predetermined plots, positioned at a height of 1.5 meters and spaced 20 meters apart. Fruit fly rearing involved collecting infested fruit using purposive sampling from the same five plots, then incubating until adult flies emerged. The fruit fly species attacking the red guava orchard was identified as Bactrocera dorsalis. Independent t-test analysis revealed significant differences between the populations of trapped fruit flies and those obtained from host rearing. The emergence rate of fruit fly adults from host rearing exhibited a negative correlation with the trapped fruit fly population, described by the regression equation Y = 359.282 – 7.2146X. Path analysis indicated that rainfall positively correlates with temperature and humidity, while temperature negatively correlates with humidity. Additionally, rainfall and humidity negatively correlate with the trapped fruit fly population, whereas temperature shows a positive correlation.